Theory and Methodology in Elías José Palti: : Towards a Historiography of Political Languages - Páez Debia, Gabriel (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2023)
This article analyzes in historiographical terms the theoretical and methodological precepts developed by the historian Elías José Palti. For this we have focused on the differences that he makes explicit between the history of ideas and intellectual history. In addition, we address the intellectual influences that are observed in the work of said historian, the dialogues, proposals and precautions that must be taken, together with the essential categories to make this type of analysis. In this sense, we highlight that this way of doing historiography has great potential due to its interdisciplinary and innovative character in interpretive terms, while on the other hand the discomfort that prompted Palti in the search for a new way of doing historiography still persists within the context Chilean, to the extent that said theoretical-methodological framework has only recently been worked on by historians from that country.
Keywords: new intellectual history; history of political languages; history of ideas; Elías José Palti